Securing Communal Land and Resource Rights in the Albertine Region of Uganda: The Case of Hoima and Buliisa Districts - Byakagaba, Patrick (CRED, 2015)
Land is essential for the livelihoods and wellbeing of rural communities and has cultural significance that may go beyond production and monetary realms. The policy and legal framework of Uganda provides for communal land tenure system but operationalization of the provisions has not taken place in many parts of the country including the oil rich Albertine region. This scenario has left communal land in this region to be perceived as “open access”, land with no defined owners - hence rendering it susceptible to land grabbers. This has not only raised anxiety within the community but is affecting the livelihoods of hundreds and thousands of the local people. It is still unclear which model of land management will ensure that communal land rights are secure amidst the current threats associated with the nascent oil and gas industry.
Keywords: Communal Land; Resource Rights; Albertine Region; Uganda